Erythema – not only ones - Wiszniewska, Magdalena; Zeman, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2011)
Erythema is a skin condition characterized by redness or rash There are many types of erythema. Erythema nodosum is the most frequent clinico-pathological variant of the septal panniculitides. The disorder is characterized by the eruption of erythematosus, tender nodules located predominantly over the extensor aspects of the lower extremities. Erythema multiforme is an acute, selflimited disease that can caused rash, skin peeling and blisters on the skin and mucosus membranes. Erythema migrans, characteristic circular skin rash is in most patients the first symptom of borreliosis. Exanthema subitum (roseola infantum), is an infectious disease of children, whose manifestations are usually limited to a transient rash that occurs following a fever of about three day’s duration. Erythema infectiosum (fifth disease) is a common childhood exanthem caused by human parvovirus B19, in which a classic 3-phased cutaneous eruption follows a rarely noticed prodrome.